Adâbî Ijtimâ’î dalam Penafsiran Ayat Gender Perspektif Muhammad Abduh - Iyam Muslimah, Siti (Green Publisher Indonesia, 2024)
The soil retaining wall is one of the reinforcements used to prevent landslides on the slope. Starting from the argument presented by Amina Wadud and Zaitunah Subhan, that one of the causes of gender bias is the dominance of men in an interpretation. So it can be assumed that the majority of male interpreters only make their experience as a single standard.However, this study shows that Muhammad Abduh's interpretation provides a balanced value in viewing gender relations verses. Thus, it comes to the argument that the social reality of society has a significant influence on a person in interpreting the Qur'an. The alarming political and societal situation encouraged Abduh to make a breakthrough and change in upholding justice. The times had a significant impact on the roles of women and men in the domestic and public spheres. This makes the interpretation of gender also undergo adjustments. This study will dissect Muhammad Abduh's thoughts on gender relations contained in his magnum opus, Tafsîr al-Manâr. The themes taken are: The Degree of Women, Women's Testimony, Polygamy, and Nusyûz Wife. In this research, the author applies a qualitative method with a pure literature study. Through analysis with adâbî ijtimâ'î theory, it can be concluded that Muhammad Abduh had a progressive view of women in Islam. He believed that women and men have equal value before God, with equal rights and obligations.